The production of silage in small containers for small farmers - Letsoalo, Mokgatsana Lerato Victoria (University of Limpopo, 2014)
The Limpopo Province is a well known for its warm summers and dry winters. The lack of rainfall in winter causes a shortage of feed for livestock and is responsible for poor animal production and even mortality. Alternatives winter feeding strategies that have been suggested by researchers are planted pastures, crop residues, hay, foggage and silage. Silage in “small container” is the cheapest potential alternative fodder source. This preliminary study investigated the use of small container silage during winter on small scale farms by using Panicum maximum, maize, pearl millet and forage sorghum. Dewageningsdrift (Hygrotech Experimental Farm, Gauteng) was used for this research project. The treatments were four crops (Maize, forage sorghum, pearl millet and Panicum maximum) ensiled in three ensiling techniques (small plastic bags, black plastic bags and buckets). During the first season (2009/2010) the samples were collected in a maturity stage. During second season (2010/2011) the samples were collected in different growing stages (soft dough, hard dough and matured stage). If all quality norms are taken into consideration maize can still be classified as a good silage crop. Silage of similar quality can be produced from forage sorghum and pearl millet. Pearl millet produced relative good quality silage when ensiled in a mature stage. Ensiling in small plastic bags and buckets resulted in good quality silage. There was a trend that buckets resulted in better quality silage when harvested in the hard dough stage. Black refuge plastic bags are not suggested for silage making. Although the quality is lower, silage can be produced from hard dough and mature material, especially with pearl millet in buckets.
Thesis (M.Sc. (Pasture Science)) --University of Limpopo, 2014
Keywords: Silage production; Silos; Silage